Importance of CALLISIA FRAGRANS in MEDICINE, PHARMACEUTICAL and Other Fields (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
This article gives information about morphological structure, medicinal properties, use in medicine, chemical composition of Callisia fragrans L. plant.  Literary information of foreign scientists about the chemical composition of the plant, the biological effect of its raw materials was analyzed.  The main pharmacological properties of the medicinal raw material Callisia fragrans L. are also described.  Information about the use of this medicinal plant in folk medicine of different countries of the world has been collected. Interestingly, this plant is a promising plant for use in official medicine in the future.